Do ser ao tornar-se professor nas escolas nos espaços de privação de liberdade - Lopes, Cloris Violeta Alves (Universidade Federal de São Carlos, 2019)
The study, From being to become teacher in places of deprivation of liberty, intended to understanding how the knowledge required for teaching, Youth and Adult Education in situation of deprivation of liberty, based on the teaching and learning processes they experience in their everyday pedagogical practices. The reason for such choices is due to the comprehension and intellectual property of each one which contemplating the enquiries and concerns about teaching young and adults and the teacher knowledge built during the performance in teaching in prisional system. One of the problem situations discussed was about continuing education, teacher knowledge and how they become teachers in the prisoner schools. In this perspective, the paper examines the following questions: What is the teacher’s knowledge of teachers who work in prisoner schools they attribute as necessary to the exercise of teaching in places of deprivation of liberty? It is a qualitative research with an emphasis on the narrative method. In this form of approach, the following methodological procedures were used: bibliographic review; participant observation, analysis of written documents, daily records, norms, laws, guidelines, didactic material; the realization of open interviews (recorded and transcribed in field notes) with a prior script. Initially, for the data collection, it was used the participant observation during the pedagogical meetings - HTPC, or ATPC - collective pedagogical work class, with fifteen teachers who worked in schools of prisional units in a city of the state of São Paulo. A brief questionnaire was applied to delineate a profile of the collaborators and, in the second stage of data collection, we used oral narratives from the experiences of three teachers who volunteered collaborator to the investigation. The results pointed out that becoming a teacher, in these places, involves coexistence with a routine surrounded by overwork; means facing challenges for the students of this system to the appropriation and development of writing, for this reason teachers learning from those challenges; means learning from interaction with their students; involves obedience to the rigid norms of imprisonment; pervades moments of stress and tension. In the second moment of the data collection, in the individual conversations with the collaborators, emerged of Individual Narratives the Guiding Axes: Trajectories of Infancy (IT); Initial Formation (IF); Beginning of teaching (ID); Become a teacher (TP). It was evidenced in teachers’ statements that there is a gap between what is proposed and what is lived. The teachers reveal that they have been building the teacher knowledge in their teaching experiences and forming themselves in practice with their peers. The data revealed, without claiming to be conclusive, it seems to point out important evidences for the construction of public policies for the continuing education of teachers who work in schools in the prisional system.
From being to become teacher in places of deprivation of liberty
Keywords: Educação escolar na prisão; Saberes docentes; Formação de professores; School in prison; Teacher knowledge; Teacher training; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO